Body Mass Index and Physical Activity of High-School Students: A Gender Study - EROĞLU, Musa; AYDIN, Savaş; OKUYUCU, Selçuk (Journal of Neonatal Surgery, 2025)
Background and Aim: This research aimed to: 1) assess the BMI and Physical Activity levels of a cohort of high school students, thereby evaluating the prevalence of underweight, overweight, and obesity; 2) analyze the physical activity levels of all participants in the study; and 3) compare BMI and physical activity between male and female students. Methods: A descriptive-comparative approach was employed in this study. The sample comprised 423 high school students, of whom 201 were female. Participants' ages ranged from 12 to 18 years, with a mean age of 15.51±0.96 years. Participants were selected through a convenience sampling method. Standard tests were used to collect data. Independent t test was used for data analysis. Results: The findings indicated that the average Body Mass Index (BMI) for male students was 23.33 (2.66) kg/m², while for female students, it was 20.99 (2.17) kg/m². The BMI values for male students ranged from 16.5 to 34.0 kg/m², whereas female students exhibited BMI values between 16.0 and 27.8 kg/m². Furthermore, the data revealed that, on average, students engaged in physical activity for approximately 5.60 (5.03) hours per week. Specifically, female students participated in physical activities for an average of 4.05 (4.32) hours, compared to male students who averaged 8.11 (5.30) hours. The findings from the independent t-test indicate that the disparities between male and female participants in the measured variables are statistically significant (p<0.05). Conclusion: The results of our study align with those of previous research; however, we identified statistically significant differences related to gender and physical activity levels. It is essential to prioritize the education of young individuals, as they are more likely to adopt and sustain healthy habits throughout their lives. These findings underscore the importance of a comprehensive strategy for the prevention and management of risk factors, especially within the youth demographic